Cultural and Technical Analysis of 12 Basic Principles of Animation in the 2D Short Film ‘Prognosis - Wahyuni E, Tulus Rega; Husna, Anisatul (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study analyzes the application of the 12 basic principles of animation in the Indonesian 2D animated short film Prognosis. Without using dialogue, the film relies entirely on visual elements to construct an emotionally rich narrative between a child and his father. Through qualitative analysis, this research identifies how animation principles such as Squash and Stretch, Anticipation, Staging, and Timing are employed to evoke empathy, tension, and resolution. The study also explores how these principles are contextualized within Indonesian cultural narratives, especially those concerning familial hierarchy, emotional restraint, and symbolic representations of motherhood and protection. The findings reveal that the animation not only demonstrates technical mastery but also conveys local values through universally resonant visual storytelling. This contributes to broader discussions on how animation serves as a medium for expressing social meaning and emotional realism.